Machine learning-based prognostic model for in-hospital mortality of aortic dissection: insights from an intensive care medicine perspective - Lei, Jiahao; Zhang, Zhuojing; Li, Yixuan; Wu, Zhaoyu; Pu, Hongji; Xu, Zhijue; Yang, Xinrui; Hu, Jiateng; Liu, Guang; Qiu, Peng; Chen, Tao; Lu, Xinwu (My University, 2024)
Aortic dissection (AD) is a severe emergency with high morbidity and mortality, necessitating strict monitoring and management. This retrospective study aimed to identify prognostic factors and establish predictive models for in-hospital mortality among AD patients in the intensive care unit (ICU).
Keywords: aortic dissection; in-hospital mortality; machine learning; blood pressure; fluid balance